1989
DOI: 10.1017/s0252921100153801
|View full text |Cite
|
Sign up to set email alerts
|

Electron temperatures of flare plasmas from emission line fluxes

Abstract: SummaryWe present spectral diagnostics for the fluxes of emission lines, in the spectral range 3600-4400 Å, during the cooling phase of stellar flares on dMe stars. Using these diagnostics, electron temperatures have been computed for flares on AD Leonis, Proxima Centauri and UV Ceti. This preliminary model assumes a single flare loop containing a homogeneous, stationary optically-thin flare plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(100 citation statements)
references
References 3 publications
8
92
0
Order By: Relevance
“…On the other hand, in stellar flares evidence of mass motions has also been reported. In particular, a large enhancement in the far blue wings of Balmer lines during the impulsive phase of a stellar flare was interpreted as a high‐velocity mass ejection (Houdebine, Foing & Rodonó 1990), or high‐velocity chromospheric evaporation (Gunn et al 1994b), and red asymmetries in the wings of Balmer lines are reported by Houdebine et al (1993) as evidence of CDC. Broadening and shifts in UV lines during stellar flares, also interpreted as mass motions, have been reported by Simon, Linsky & Schiffer (1980), and Linsky et al (1989).…”
Section: Description Of the Flarementioning
confidence: 96%
“…On the other hand, in stellar flares evidence of mass motions has also been reported. In particular, a large enhancement in the far blue wings of Balmer lines during the impulsive phase of a stellar flare was interpreted as a high‐velocity mass ejection (Houdebine, Foing & Rodonó 1990), or high‐velocity chromospheric evaporation (Gunn et al 1994b), and red asymmetries in the wings of Balmer lines are reported by Houdebine et al (1993) as evidence of CDC. Broadening and shifts in UV lines during stellar flares, also interpreted as mass motions, have been reported by Simon, Linsky & Schiffer (1980), and Linsky et al (1989).…”
Section: Description Of the Flarementioning
confidence: 96%
“…Giampapa et al (1982) used Ca II observations to model M dwarf chromospheres, with limited success. Houdebine & Panagi (1990) investigated the effects of changing the model hydrogen atom used in the calculations, but they did not fit their models to data. Hawley & Fisher (1994) have developed chromospheric flare models, which incorporate a full nonlocal thermodynamic equilibrium (NLTE) treatment of the statistical equilibrium and radiative transfer in the important optically thick chromospheric lines and a helium ionization equilibrium computed self-consistently with the downward X-ray flux from the corona.…”
Section: Stellar Activitymentioning
confidence: 99%
“…The asymmetries of the Balmer lines are usually interpreted as a consequence of plasma turbulence or directed mass motions. Houdebine et al (1990) found a large enhancement in the far blue wings of Balmer lines during the impulsive phase of a flare on AD Leo, that they attribute to a mass ejection. Houdebine et al (1993) found in the same flare redshifted Balmer line cores that were interpreted as a chromospheric downward condensation.…”
Section: Hα Line Asymmetries: Possible Mass Ejectionmentioning
confidence: 95%